Distension‐evoked motility analysis in human esophagus. Issue 5 (29th January 2013) - Liao, D.; Villadsen, G. E.; Gregersen, H.
Abstract Background The major function of the esophagus is to transport food from the mouth to the stomach by peristaltic muscle action. However, only few techniques exist for detailed evaluation of motor activity of the esophagus in vivo. The aim of this study is to use distension combined with manometry and impedance planimetry [pressure–cross‐sectional area (P‐CSA) recordings] to assess esophageal peristaltic motor function in terms of the mechanical energy output, and to examine the change in the motor activity of the esophagus in response to butylscopolamine, an anticholinergic drug known to impair the smooth muscle contraction in the gastrointestinal tract. Methods The probe with CSA measurements was positioned 7 cm above the lower esophageal sphincter in 16 healthy volunteers before and during butylscopolamine administration. Distension‐evoked esophageal peristalsis was analyzed using P‐CSA data during distension up to pressures of 5 kPa. The P‐CSA, work output (area of the tension‐CSA curves), and propulsive tension were analyzed. Key Results The wave‐like peristalsis resulted in P‐CSA loops consisting of relaxation and contraction phases. The work increased with the distension pressure (from 1311 ± 198 to 16 330 ± 1845 μJ before butylscopolamine vs from 2615 ± 756 to 11 404 ± 1335 μJ during butylscopolamine administration), and propulsive tension increased from 18.7 ± 1.9 to 88.5 ± 5.5 N m−1 before the drug and from 23.1 ± 3.9 to 79.5 ± 3.3 N m−1 during butylscopolamine administration). Significantly, lower values were found during butylscopolamine administration compared with the distension before using the drug (P < 0.01). Conclusions & Inferences Esophageal muscle properties during peristalsis can be assessed in vivo in terms of mechanical energy output parameters. Butylscopolamine impaired muscle contraction which could be detected as altered contraction parameters. The analysis can be further used as an adjunct tool of the combined manometry and impedance planimetry recordings to derive advanced esophageal motor function parameters for studying the physiological and pathophysiological mechanical consequences of esophageal contractions.